Non-invasive Respiratory Support in Blunt Chest Injury - T. V. Lobus; Yu. V. Marchenkov; V. V. Moroz (Общая реаниматология)
Objective. To optimize the results of treatment in patients with acute respiratory failure (ARF) due to lung contusion, by using the methods of non-invasive mask respiratory support. Materials and methods. The study covered 31 patients with severe blunt chest injury, multiple costal fractures, and hypoxemic ARF. The patients underwent assisted ventilation (AV) in the CPAP+PSV mode through a facial or nasal mask. Physiological parameters were recorded during non-invasive mask ventilation (NIMV) in the stepwise fashion. A control group comprised 25 patients with the similar severity of injury and ARF who were given conventional AV.Results. In 67.7% of the study group patients, NIMV was effective in improving oxygenation and external respiration, without exerting negative hemodynamic effects. Endotracheal intubation and AV could be avoided in these patients. Comparison of the study and control groups revealed a significant reduction in the incidence of secondary pneumonias in the NIMV group and in the duration of treatment. Mask ventilation could decrease mortality from 44% in the control group to 9.7% in the NIMV group.Conclusion. NIMV applied to patients with hypoxemic ARF in the presence of lung contusion improves pulmonary function and, in the bulk of patients, allows endotracheal intubation and AV and consequently their associated complications. When mask ventilation is employed, management of patients becomes shorter and simpler and mortality rates substantially decrease.